Gender- and youth-sensitive data collection tools to support decision making for inclusive sustainable agricultural intensification - Grabowski, P.P.; Djenontin, I.; Zulu, L.; Kamoto, J.; Kampanje-Phiri, J.; Darkwah, A.; Egyir, I.; Fischer, Gundula (Informa UK Limited, 2021)
To achieve equitable sustainable agricultural intensification (SAI), it is essential to understand differential access and control over agricultural resources by women and youth, and to assess how intensification interacts with gendered and age-dependent relationships. Existing packages for assessing women’s empowerment in agriculture tend to be large-scale surveys that do not provide timely results, nor are they easily integrated into a gender-transformative process. This paper applies concepts from Kabeer on gender analysis and empowerment to evaluate promising tools available for assessing inequities in SAI and supporting a gender-transformative approach. We interviewed decision makers in Malawi and Ghana to understand their needs and practices for equityanalysis. We evaluated, adapted and tested tools to detect inequities from SAI. Our results demonstrate the suitability of tools to decision makers’ needs for ex-ante assessment and early detection of disparities. We synthesize information from the testing and adaptation of tools about the resources required, the equity issues they can reveal and their potential role in a gender-transformative approach. The use of the tools needs to be part of an inclusive and culturally specific process for identifying gaps and facilitating a more equitable sharing of SAI responsibilities and benefits through iterative cycles of action and learning.